2019
DOI: 10.1021/acsaem.9b00608
|View full text |Cite
|
Sign up to set email alerts
|

Record-Efficiency n-Type and High-Efficiency p-Type Monolike Silicon Heterojunction Solar Cells with a High-Temperature Gettering Process

Abstract: We report independently confirmed 22.15% and record 22.58% power conversion efficiencies, for thin (130 μm-140 μm) p-and n-type mono-like Si solar cells, respectively. We comparatively assessed advanced n-type and p-type mono-like silicon wafers for potential use in low-cost high-efficiency solar cell applications by using phosphorus diffusion gettering for material-quality improvement and silicon heterojunction solar cell fabrication for assessment of performance in high-efficiency photovoltaic device archite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…For instance, Jay et al 96 demonstrated that large‐area n‐type a‐Si:H/c‐Si heterojunction solar cells using cast mono‐like silicon wafers as substrate can achieve efficiency over 21.5%, of which the I – V curve is shown in Figure 27. Kivambe et al 97 also reported a record efficiency of 22.58% and 22.15% for n‐type and p‐type cast mono‐like silicon‐based hetero‐junction solar cells on small area, respectively. It is worth noting that the n‐type and p‐type cast mono‐like silicon wafers were P‐diffusion gettered before cell fabrication processes, and therefore, the wafer quality was much improved for the record hetero‐junction solar cells.…”
Section: Cell Efficiency Potential Of Cast Mono‐like Siliconmentioning
confidence: 97%
“…For instance, Jay et al 96 demonstrated that large‐area n‐type a‐Si:H/c‐Si heterojunction solar cells using cast mono‐like silicon wafers as substrate can achieve efficiency over 21.5%, of which the I – V curve is shown in Figure 27. Kivambe et al 97 also reported a record efficiency of 22.58% and 22.15% for n‐type and p‐type cast mono‐like silicon‐based hetero‐junction solar cells on small area, respectively. It is worth noting that the n‐type and p‐type cast mono‐like silicon wafers were P‐diffusion gettered before cell fabrication processes, and therefore, the wafer quality was much improved for the record hetero‐junction solar cells.…”
Section: Cell Efficiency Potential Of Cast Mono‐like Siliconmentioning
confidence: 97%
“…A subsequent low-temperature hydrogen passivation process can then be used to passivate boron-oxygen defects, thereby eliminating light-induced degradation (LID), one of the key arguments in heading to the use of n-type wafers and the SHJ technology. [1,11,35] Figure 1 shows a comparison of the process flow for SHJ and PERC solar cells, highlighting the natural incorporation of defect engineering in the PERC process flow.…”
Section: Doi: 101002/pssr202100170mentioning
confidence: 99%
“…Kivambe et al demonstrated high efficiencies in both p‐type and n‐type cast mono wafers using a defect engineering approach prior to SHJ cell fabrication. [ 35 ] Cast mono or quasi‐mono wafers are formed via the solidification of molten silicon in a crucible with a partially melted silicon seed crystal. This approach produces wafers that are higher quality than the standard multicrystalline wafers formed via casting and has cost benefits compared to the conventional Cz growth process.…”
Section: Defect Engineering Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…The solar cells, which can directly convert sunlight into electrical energy, are undoubtedly the core device of photovoltaic power generation, where the single crystal silicon (sc-Si) solar cell occupied more and more market share due to the continuous technological progress and cost reduction [4,5]. Moreover, the n type silicon show huge potential in developing low-cost and high-efficiency solar cells in the future due to its natural advantages of low light attenuation, high minority carrier lifetime [6,7]. Surface texture is an important optical management strategy for high-efficient silicon solar cell devices [8].…”
Section: Introductionmentioning
confidence: 99%